СОЦИО-КУЛЬТУРНАЯ И ЛИНГВИСТИЧЕСКАЯ СОСТАВЛЯЮЩИЕ ЛИТЕРАТУРНОЙ РЕЧИ ЖИТЕЛЕЙ г. СОЛИКАМСКА (Filološke pripombe, 2019)
In article the sociocultural and linguistic component of speech of residents of Solikamsk of Perm region is discussed. The brief information in many respects explaining the developed language's culture of the city is given. The considerable stratum of lexical units of dialect origin is shown. The model of proficiency in a language is constructed by a local word. Research showed that the use of lokalizm (local word) in literary speech depends on various social factors; it is connected with unevenness of development of language in time and space.